Primaquine Diphosphate, a Known Antimalarial Drug, Blocks Vascular Leakage Acting Through Junction Stabilization - Noh, Minyoung; Zhang, Haiying; Kim, Hyejeong; Park, Songyi; Kim, Young-Myeong; Kwon, Young-Guen (Frontiers in Pharmacology, 2021)
Endothelial barrier integrity is important for vascular homeostasis, and hyperpermeability participates in the progression of many pathological states, such as diabetic retinopathy, ischemic stroke, chronic bowel disease, and inflammatory disease. Here, using drug repositioning, we discovered that primaquine diphosphate (PD), previously known as an antimalarial drug, was a potential blocker of vascular leakage. PD inhibited the linear pattern of vascular endothelial growth factors (VEGF)-induced disruption at the cell boundaries, blocked the formation of VEGF-induced actin stress fibers, and stabilized the cortactin actin rings in endothelial cells. PD significantly reduced leakage in the Miles assay and mouse model of streptozotocin (STZ)-induced diabetic retinopathy. Targeted prediction programs and deubiquitinating enzyme activity assays identified a potential mechanism of action for PD and demonstrated that this operates via ubiquitin specific protease 1 (USP1). USP1 inhibition demonstrated a conserved barrier function by inhibiting VEGF-induced leakage in endothelial permeability assays. Taken together, these findings suggest that PD could be used as a novel drug for vascular leakage by maintaining endothelial integrity.